Psychological Impact of Acne Vulgaris Among Adolescents and Adults Attending a Tertiary Care Hospital - Dhunna, Himanshu; K. Jhad, Manthankumar; Hassan, Syed Belal; Agrawal, Anurag; Karim, Md. Faizi; Anwar, Shadma (Journal of Neonatal Surgery, 2025)
Background: Acne vulgaris is a prevalent dermatological condition among adolescents and adults, with psychological effects that are often under-recognized in clinical settings. It can lead to significant mental health issues such as anxiety, depression, and low self-esteem, regardless of clinical severity. Objectives: To assess the psychological impact of acne vulgaris using standardized tools and to evaluate the relationship between acne severity and levels of anxiety, depression, and self-esteem. Methods: A cross-sectional observational study was conducted from March to June 2025 in the Dermatology OPD of a tertiary care hospital in Lucknow. A total of 160 patients aged 15–35 years with clinically diagnosed acne were enrolled through consecutive sampling. Acne severity was assessed using the Global Acne Grading System (GAGS), while psychological parameters were evaluated using the Hamilton Anxiety Rating Scale (HAM-A), Hamilton Depression Rating Scale (HAM-D), and Rosenberg Self-Esteem Scale (RSES). Data were analysed using SPSS version 24. Results: Moderate acne was the most common (51.9%). Moderate-to-severe anxiety and depression were observed in 47.5% and 28.75% of participants, respectively, while 51.25% had low self-esteem. Acne severity showed a strong positive correlation with anxiety (r = 0.52) and depression (r = 0.47), and a negative correlation with self-esteem (r = –0.41), all statistically significant (p < 0.001). Females had significantly higher anxiety and depression scores and lower self-esteem than males (p < 0.05). Conclusion: Acne vulgaris significantly affects psychological well-being. Routine mental health assessment should be integrated into acne management, especially in high-risk groups such as females and those with moderate-to-severe acne.